Prognostic value of nutritional and hematologic markers in head and neck squamous cell carcinoma treated by chemoradiotherapy. Issue 2 (February 2016) - Moon, Hyun; Roh, Jong-Lyel; Lee, Sang-wook; Kim, Sung-Bae; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon
Abstract: Purpose: Malnutrition and systemic lymphopenia are common in many cancers and are associated with tumor progression. The purpose of this study was to investigate the prognostic values of nutritional and hematologic markers in patients with head and neck squamous cell carcinoma (HNSCC). Methods: This prospective study included 153 patients with treatment-naïve HNSCC who underwent definitive chemoradiotherapy. Body weight, serologic and hematologic parameters were measured at baseline and after 2 months of treatment. Univariate and multivariate analyses using Cox proportional hazards model were used to identify predictors of progression-free survival (PFS), cancer-specific survival (CSS), and overall survival (OS). Results: Body weight, body mass index (BMI), serum albumin, total serum proteins, hemoglobin, and circulating neutrophil, lymphocyte, monocyte, and platelet counts significantly decreased, but neutrophil–lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR) significantly increased after 2 months of treatment ( P < 0.05 each). Multivariate analyses showed that pretreatment hypoalbuminemia and high NLR were independent predictors of PFS ( P < 0.01 each). ECOG performance status, BMI < 18.5 kg/m 2 and NLR were independent predictors of CSS and OS ( P < 0.01 each). Conclusions: Our data support the evidence that several nutritional and hematologic markers are associated with the prognosis of HNSCC.